The Correlation Between Parental Attention and Learning Motivation with Mathematics Learning Outcomes of Class X SMA Negeri 3 Palangka Raya - Widiawanty, Miranty Anjely; ., Suparman; Artuti, Emy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2024)
This research is motivated by mathematics learning outcomes of students in Class X SMA Negeri 3 Palangka Raya which is still relatively low. The research aims to find out: 1) the relationship of parental attention to the mathematical learning outcomes of students in Class X SMA Negeri 3 Palangka Raya. 2) The relationship of student learning motivation with mathematics learning outcomes of Class X students of SMA Negeri 3 Palangka Raya. 3) the relationship of parental attention and student learning motivation with mathematics learning outcomes of Class X students of SMA Negeri 3 Palangka Raya. This research uses a quantitative approach with the type of correlational research. The population is all students of Class X of SMA Negeri 3 Palangka Raya in the academic year 2023/2024. 247 students were selected as a sample using cluster random sampling techniques. The instruments used were the parental attention questionnaire with 28 valid statements (= 0.83), motivation learning questionnaire with 28 valid statements (= 0.71), and the mathematics learning outcomes test with 32 valid questions (=0.81). Prerequisite test parametric statistical analysis to test the normality of parental attention data, learning motivation, and mathematical learning outcomes data with a significant level of 5% obtained all data with normal distribution. The results showed: (1) there is a positive and significant relationship between parental attention with mathematical learning outcomes with 0.19; (2) there is a positive and significant relationship between learning motivation with mathematical learning outcomes with 0.21; (3) there is a positive and significant relationship of parental attention and learning motivation with mathematical learning outcomes with = 0.25.